Natural Products That Target Virulence Factors in Antibiotic-Resistant Staphylococcus aureus - Wu, Shuai-Cheng; Liu, Fei; Zhu, Kui; Shen, Jian-Zhong (Journal of agricultural and food chemistry, 2019)
The increase in the incidence of antibiotic-resistant ( ) associated infections necessitates the urgent development of novel therapeutic strategies and antibacterial drugs. Antivirulence strategy is an especially compelling alternative strategy due to its low selective pressure for the development of drug resistance in bacteria. Plants and microorganisms are not only important food and medicinal resources but also serve as sources for the discovery of natural products that target bacterial virulence factors. This review discusses the mechanisms of the major virulence factors of , including the accessory gene regulator quorum-sensing system, bacterial biofilm formation, α-hemolysin, sortase A, and staphyloxanthin. We also provide an overview of natural products isolated from plants and microorganisms with activity against the major virulence factors of and their adjuvant effects on existing antibiotics to overcome antibiotic-resistant . Finally, the limitations and solutions of these antivirulence compounds are discussed, which will help in the development of novel antibacterial drugs against antibiotic-resistant .